Molecular Identification of Sarcocystis Species Infection in Sheep in Karbala Governorate – Iraq (Medico Legal Update, 2020)
Sarcocystis spp. are causative agents of ovine muscular stiffness, myopathies and/or inflammations of the mucosa of the intestine, , diaphragm Heart and skeletal muscles , which are generate important economic loss when causing clinical and subclinical cases, ovine Sarcocystis spp. are a protozoan parasite of worldwide distribution transmitted by canids, most commonly associated with subclinical infection in sheep, our study were described in unorganized five different localities in Karbala governorate for sheep Sarcocystis spp. investigation and classified in to two ages groups, less than 18 months-old and over 18 months-old, Macroscopic and microscopic and certain biochemical tests were used for parasite observation, Molecular assay PCR assay was used to confirm this protozoan, Currently, PCR assay based on certain regions of the cytochrome oxidase 1 sequences is considered and used widely as an inexpensive, rapid and precise molecular approach to identify the Sarcocystis spp.